THE INFLUENCE OF ENTREPRENEURIAL MOTIVATION AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP IN UNPAM ACCOUNTING STUDY PROGRAM STUDENTS - Sadiqin, Amin (Transpublika Publisher, 2024)
The main goal of this study is to investigate how entrepreneurial motivation and family environment impact the enthusiasm for entrepreneurship among students in the Unpam Accounting program. For this investigation, the Lemeshow formula was utilised, resulting in a sample size of 100 participants with a margin of error of 10%. The primary data for this study was gathered through surveys. The data was then analysed using SPSS version 26 software. The findings revealed that: 1) The individual effect of entrepreneurial motivation (X1) on the interest in entrepreneurship (Y) for Unpam Accounting students was positive and significant; 2) The individual impact of family environment (X2) on interest in entrepreneurship (Y) for Unpam Accounting students was also positive and significant; 3) Both entrepreneurial motivation (X1) and family environment (X2) together had a positive and significant impact on interest in entrepreneurship (Y) for Unpam Accounting students; and 4) The combined influence of entrepreneurial motivation (X1) and family environment (X2) on interest in entrepreneurship (Y) among Unpam Accounting students was 54%, leaving 46% potentially affected by external factors not explored in this study.